Best Practices in Solution Sales Management: a multiple case study - Müller, Björn-Christian (My University, 2015)
The competitive situation for companies steadily increases due to market saturation, commodization of products, and globalization; resulting in fierce price competition. In this context, companies move from offering products to solutions in order to overcome shrinking profit margins. Solution providers offer tailored answers to customer problems that create superior value with the intention to participate in customer success. However, it is necessary to convince customers of the offering’s impact by providing tangbile evidence through quantifying its value prior to implementation. This study aims to shed light on the function of value quantification in solution sales as well as identifying best practices solution providers make use of in the sales process. Various scholars have investigated the solution sales process. However, value quantification is typically regarded as a process element, though it is described as a separate process in the value-based selling literature. Accordingly, the thesis investigates the existing literature on solution sales management and value-based selling in order to create a comprehensive understanding of the phenomenon by indentifying and integrating various value quantification and solution sales processes into an inclusive framework, which serves as basis for empirical data collection. The empirical study comprises multiple case companies operating in the capital goods manufacturing industry. Subsequently, a cross case analysis is conducted aiming at identifying best practices and discussing those in the setting of the solution sales process. The study identifies 31 best practices in solution sales management that are put into context with the developed solution sales process model. The value of this study is its inclusiveness regarding theoretical background and managerial practices, offering new insights in the practical application of value-based solution sales approaches.
Keywords: Solution sales; Value quantification; Sales process; Best practice; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in Strategic Management|